Pengaruh Logic Exercises Terhadap Disorientasi Moral Jugdment Mahasiswa: Studi Kasus Terorisme - Selly Rahmawati (Jurnal Moral Kemasyarakatan, 2018)
The existence of the phenomenon of Indonesian citizens who joined ISIS, the number of teens who become "bride" Islamic worshipers and teenagers orientation that supports the defense of religion by radical is an indication there is a judgment about the moral disorientation of terrorism in Indonesian teenagers. Logic exercises can embed logic values which someone can take a moral decision and act logically. That is why the researcher conducting research on the influence toward logic exercises on moral judgment disorientation terrorism case study students to design an appropriate solution to the problem of moral disorientation student judgment in the case of terrorism. Testing the influence of logic exercises against the judgment of moral disorientation of the students is done by using a quasi-experimental study used data collection techniques and tools in the form of documentation, and questionnaires. The research instrument in this study is the logic exercises student worksheets, assessment rubrics Questionnaire DIT and moral judgment. The data analysis technique used in this study is the technique of quantitative analysis using independent sample t-tes. The results showed that there are differences in moral judgment ability of PGSD UPY students which use logic exercises method. Moreover, it can also be concluded logic exercises method is effective in improving PGSD UPY students moral judgment.